Students Perceptions on the quality of clinical supervision among the 12 affiliated hospital of Medical Faculty of UNISSULA - Rahmawatie, Dian Apriliana; Rahayu, Gandes Retno; Prihatiningsih, Titi Savitri (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2011)
Background: Clinical supervision has a vital role in the learning process of undergraduate medical education because it may improve the student’s clinical performance of the students. Supervision is a complex activity and covers wide variety of applications. Medical faculty of Islamic Sultan Agung University has 15 affiliated hospitals for its clinical education. To assure the quality of the clinical program, an evaluation on the quality of clinical program is required. This study was conducted to assess the effectiveness of the clinical supervision among the 12 affiliated hospitals.Design and Methods: This study involved 181 students of clinical internship of the year 2003, 2004 and 2005 of medical faculty of Islamic Sultan Agung University having the clinical rotation at the stage of surgery, obsgyn, pediatrics, internal medicine, ENT, neurology, dermatology and venerology, psychiatry, across the affiliated hospitals. The subject were divided into groups based on the hospital they were placed. Clinical Teaching Effectiveness Instrument (CTEI) adapted in bahasa Indonesia was used. The Descriptive and Kruskal-Wallis test were applied for the data analysis.Results: Means of the effectiveness of clinical supervision for 12 affiliated hospitals ranged from 3.25 to 4.02. Kruskal-Wallis test resulted in the value of Chi-S=13.32 and p=0.27.Conclusion: Over all the clinical supervision for the 12 affiliated hospitals is perceived good and shows no significant difference. However the practice of clinical supervision varies among the hospitals (Sains Medika, 3(2):135-149).